Changes in Antibiotic Resistance Patterns Before and During the COVID-19 Pandemic in Hospitalized Children at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Kitty, Winnie; Iriani, Yulia; Karmila, Ariesti (Universitas Airlangga, 2025)
Highlights: Antibiotic resistance patterns before and during COVID-19 have changed. There was an increase in MDR, MRSA, ESBL, and CRE isolates. Abstract Introduction: The coronavirus disease (COVID-19) pandemic has influenced antibiotic usage patterns due to overlapping clinical symptoms between viral and bacterial infections. This may lead to inappropriate antibiotic prescriptions, thereby increasing antimicrobial resistance. This study examined antibiotic resistance patterns in hospitalized children before and during the COVID-19 pandemic, highlighting their clinical and epidemiological significance. Methods: This was a retrospective cross-sectional study using secondary data from the Central Laboratory Installation at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. All patients aged 1 month to 18 years old with blood cultures and antibiotic sensitivity test results were included. The data were analyzed using Chi-square and linear regression in Microsoft Excel and the International Business Machines Corporation (IBM) Statistical Package for the Social Sciences (SPSS) version 26.0 for Windows. Results: The proportion of Gram-positive bacterial isolates increased from 66% before the pandemic to 75% during the pandemic. The proportion of multidrug-resistant (MDR) isolates rose from 71.7% to 74.3%. Methicillin-resistant Staphylococcus aureus (MRSA) isolates rose from 20.6% to 25.8%. The proportion of extended-spectrum beta-lactamase (ESBL) isolates increased from 81.8% to 88.9%. All Enterobacteriaceae isolates were carbapenem-resistant Enterobacteriaceae (CRE). Significant resistance changes were observed in S. aureus to oxacillin. Conclusion: There was a change in antibiotic resistance patterns during the pandemic. These findings are crucial for antibiotic stewardship and clinical policy-making.